A Conversation about “Editing” Plurilingual Scholars’ Thesis Writing - Corcoran, James; Gagné, Antoinette; McIntosh, Megan (Discourse and Writing/Rédactologie, 2018)
Drawing on our combined experiences providing thesis writing support, we critically consider the tensions surrounding policies and practices aimed at plurilingual graduate students using English as an additional language (EAL). Our trioethnographic methodology allows us to unpack and explore the ethics framing our individual “editing” practices amid institutional norms, expectations and ideologies. Drawing on relevant literature in the field, our conversations or “trialogues” produce insights and raise questions surrounding the ethical imperative of providing effective thesis writing support for plurilingual EAL writers in an era of increasing internationalization. We conclude with suggestions for flexible, targeted writing support that challenges narrow epistemologies and stale ideologies regarding taboo editing practices of academic and language literacy brokers involved in the production and revision of thesis writing.